Boundary Management Developing Business Architectures for Innovation - Kodama, Mitsuru; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Business architecture" is a concept for optimizing corporate boundaries aimed at realizing targeted business models and corporate system design involving stakeholders. To optimize the corporate boundaries, companies must partially and/or wholly optimize the individual management elements s (strategy, organization, technology, operation, and leadership) comprising the corporate system that has achieved congruence with its environment. The type of management concerned with optimizing these corporate boundaries and the corporate systems that consist of individual management elements is referred to in this book as "boundary management." The concept of "boundaries congruence" inside and outside the corporate system, and the formation of an optimal architecture concerned with environmental change and with management elements such as strategy, organization, technology, operation, and leadership are key to implementing dynamic strategic management. This book presents the concept of "business architecture" and optimizing processes as a corporate system based on multiple corporate case studies (Sony, NTT-DATA, NTT-DoCoMo, Toyota, Honda, Omron, Takara, Recruit, First Retailing, Panasonic, and Canon).
Dynamic View of Strategic Management -- Theoretical Framework of Dynamic Strategic Management Through Boundary Management -- Developing New Business Models Through Dynamic Boundary Management: Case Studies of Sony and NTT-DATA -- Developing New Broadband Services by Dynamic Collaboration Through Strategic Boundary Networks: A Case Study of NTT DoCoMo -- New Knowledge Creation Through Leadership-Based Strategic Community -- New Theoretical Framework and Insights Derived from Comparative Case Studies -- Theoretical and Managerial Implications -- Conclusion.
Keywords: Economics; Business planning; Technology; Economics/Management Science; R & D/Technology Policy; Technology Management; Organization/Planning.